European integration directions of development of the transport industry of Ukraine - Kersys, Robertas; Pererva, P. G. (Харківський національний університет імені В. Н. Каразіна, 2024)
The report proves the need to reform the transport sector, in particular through the improvement of state regulation and its institutional and functional support. EU member states have common standards on technical, security and social requirements, state support and market liberalization in sectors such as road transport, railways, inland waterways, aviation and maritime transport.
Євроінтеграційні напрями розвитку транспортної галузі України
Keywords: transport industry; Ukraine; reform; Europe; integration; standards; railway; requirements